Two Paradigms of Economic Development in CEE Countries - Gylys, Povilas (Ekonomika, 2004)
The direction of economic development depends on the paradigmatic framework in which economic reality is perceived. In the framework of holistic paradigm also public and not only private goods are understood as economic goods. Correspondingly, the public sector is enclosed into economy. The individualistic approach presupposes reduction of economic reality to market and overtly or covertly negative attitude towards public sector as non-economic. The phenomenon of reflexiveness is present here. Methodological holism and methodological individualism give birth to different strategies of economic policy and finally lead to different outcomes of economic development.